Near-infrared Raman spectroscopy to detect anti-Toxoplasma gondii antibodies in blood sera of domestic cats - Duarte, J.; Tadeu, M.; Pacheco, T.; Silveira, L.; Machado, R. Z. [UNESP]; Martins, R. A.; Zangaro, R. A.; Villaverde, A. Balbin (SPIE, the international society for optics and photonics, 2001)
Near Infrared (NIR) Raman Spectroscopy has been study for the last years for many biomedical applications. It is a powerful tool for biological materials analysis. Toxoplasmosis is an important zoonosis in public health, being the cats the principal responsible for the transmission of the disease in Brazil. The objective of this work is to investigate a new method of diagnosis of this disease. NIR Raman Spectroscopy was used to detect anti Toxoplasma gondii antibodies in blood sera from domestic cats, without sample preparation. In all, six blood serum samples were used for this study. A previous serological test was done by the Indirect Immunoenzymatic Assay (ELISA) to permit a comparative study between both techniques and it showed that three serum samples were positive and the other three were negative to toxoplasmosis. Raman spectra were taken for all the samples and analyzed by using the Principal Components Analysis (PCA). A diagnosis parameter was defined from the analysis of the second and third principal components of the Raman spectra. It was found that this parameter can detect the infection level of the animal. The results have indicated that NIR Raman Spectroscopy, associated to the PCA can be a promising technique for serological analysis, such as toxoplasmosis, allowing a fast and sensitive method of diagnosis.
Keywords: Disease diagnosis; NIR Raman spectroscopy; PCA method; Serological analysis; Toxoplasmosis